Analisis Sistem Akuntansi Utang Piutang Studi Kasus Pada PT. Rapitama Intertech Buana - Souhoka, Bagas Adiansyah; Fadillah, Rama Afan; Meldiansah, Reza; Fathan, Muhammad; Runtuwene, Faithly Jabez Jefune; Fauziyah, Fauziyah (JAIS - Journal of Accounting Information System, 2024)
Rapitama Intertech Buana is a company operating in the interior and exterior contractor sector located in Cibubur, Indonesia. The company's primary focus is creating unique and functional interior design solutions in collaboration with clients. An effective and efficient accounting system for managing finances is very important for companies. This research aims to provide an overview of how companies manage their debts and liabilities, and whether the system implemented helps achieve long-term financial goals. The research found that companies still use manual transaction recording systems on payables and accounts payable. Therefore, the research team developed an application prototype for recording transactions and debt management, as well as increasing efficiency and data organization.